Oral and anal sex are key to sustaining gonorrhoea at endemic levels in MSM populations: a mathematical model. (16th January 2015) - Hui, B; Fairley, C K; Chen, M; Grulich, A; Hocking, J; Prestage, G; Walker, S; Law, M; Regan, D
Abstract : Objectives: Despite early treatment of urethral infection, gonorrhoea is endemic in urban populations of men who have sex with men (MSM) in Australia. By contrast, gonorrhoea is not common in urban heterosexual populations. Sexual activities among MSM usually involve anal or oral sex, and as these behaviours are becoming increasingly common among heterosexuals, there is a need to investigate their roles in transmission of gonorrhoea. Methods: We developed individual-based models of transmission of gonorrhoea in MSM and heterosexuals that incorporate anatomical site-specific transmission of gonorrhoea. We estimated the probabilities of transmission for anal sex and oral sex by calibrating an MSM model against prevalence of gonorrhoea and sexual activity data. These probabilities were then applied to a heterosexual model in order to examine whether gonorrhoea can persist in a heterosexual population through the addition of anal sex and oral sex. Results: In the MSM model, gonorrhoea can persist despite prompt treatment of urethral infections. The probability of gonorrhoea persisting is reduced if use of condom for oral sex is increased to more than 15% of acts. Assuming that treatment of symptomatic infections is prompt, gonorrhoea is unlikely to persist in a heterosexual population even with the addition of anal and oral sex. Conclusions: Our models suggest that oral sex has an important role in sustaining gonorrhoea in a population of MSM by providing a pool of untreated asymptomatic infection. The importance of anal sex or oral sex in sustaining gonorrhoea in a heterosexual population remains uncertain due to the lack of information linking different types of sex acts and transmissibility.